PERANCANGAN STRUKTUR HOTEL AMARIS SIMPANG LIMA SEMARANG - Ridwan Ruslan Setiaji; Okky Nugroho Budiandono; Nuroji Nuroji; Himawan Indarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Structural Design of Amaris Hotel Simpang Lima Semarang designed with SNI 2847-2013 and SNI 1726-2012. Seismic analysis using dynamic respons spectrum method. Seismic forces calculated based on area of the earthquake zone 4 as the region has a fairly large earthquake acceleration, so it must be designed earthquake-resistant structures. Included in Seismic Design Criteria Type D so that the planning system used method with special moment resisting frames system (SMRFS). Frame system is composed of a framework of beams and columns, where the columns are made stronger than the beam (strong column weak beam). To avoid failure of the structure at the beam-column joint, plastic form joint is planned to occur in the beams and columns only occur at the top of the column foundation. Structure analysis using anayisis structure program to help modeling the structure and determine the forces acting on the structure. Materials used are concrete f'c 25 MPa, where as for steel reinforcement plates and stirrup fy 240 MPa and longitudinal bar fy 400 MPa.